ENHANCING READING SKILLS THROUGH ONLINE ENGLISH MAGAZINES AMONG JUNIOR HIGH SCHOOL STUDENTS - Yulia Wiranti; Sherly Kurniawati; Mike Nurmalia Sari (Dharmas Education Journal (DE_Journal), 2026)
This study investigated the effectiveness of using online English magazines to enhance reading skills and motivation among junior high school students. A quasi-experimental design was employed, involving an experimental group (n=25) that utilized online magazines and a control group (n=26) that followed traditional methods. Pre- and post-test scores, along with motivation questionnaires, were administered. Results from an independent samples t-test revealed a statistically significant improvement in reading scores for the experimental group (+16.5 mean gain) compared to the control group (+5.6 mean gain). Furthermore, ANCOVA confirmed this significant difference in post-test scores even after controlling for initial abilities. The motivation questionnaires indicated that students in the experimental group experienced increased motivation toward reading English texts, finding the content more engaging, relevant, and enjoyable than traditional textbooks. These findings suggest that integrating online English magazines is an effective and engaging pedagogical tool for improving both reading proficiency and intrinsic motivation in junior high school English language learning.